PENGARUH PEMBERIAN PUPUK ORGANIK CAIR (POC) TOP G2 DAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Sulasmi Sulasmi; Safruddin Safruddin; Rita Mawarni (Universitas Asahan, 2020)
This research was carried out in the research field of the Faculty of Agriculture, Asahan University with a height of 10 m above sea level, climate type C (oldeman). The study was conducted from January to March 2019. The research materials consisted of Bima Brebes variety of shallot seed tubers, dried chicken manure, Top G2 organic liquid fertilizer, Deltamethrin active ingredient (Decis 2.5 EC), fungicidal active ingredients Mankozed (Decis 2.5 EC) Dithane M-45 80 WP) and water. The research tools used were hoes, rakes, tripe machetes, torches, raffia ropes, knives, gauges, schalifers, calculators and other stationery, title boards, sample plant plates, bloated, and treatment boards. This research was arranged based on a factorial randomized block design (RBD) consisting of 2 treatment factors and 3 replications. The first factor is the application of POC top G2 fertilizer with 4 levels, namely: P0 = 0 cc / liter of water, P1 = 4 cc / liter of water, P2 = 8 cc / liter of water, P3 = 12 cc / liter of water. The second factor is the provision of cow manure with 3 levels, namely: A0 = 0 tons / ha, A1 = 5 tons / ha, A2 = 10 tons / ha. The results showed that the best application of top G2 POC fertilizer was obtained at a dose of 12 cc / liter of water / plot resulting in a plant height of 25.56 cm, a total tuber crop of 7.96 cloves, a crop production of 63.52 g, production per plot of 1.27 kg. The best application of cow manure is obtained at a dose of 10 kg / ha = 1 kg / plot resulting in a plant height of 27.39 cm. number of crop tubers 8.38 cloves, production per plant 62.21 g, production per plot 1.25 kg. The interaction between the application of top G2 POC fertilizer and chicken manure on the growth and production of shallot plants showed no significant effect on all parameters observed.